Hubungan Antara Self Efficacy Dengan Quarter Life Crisis (QLC) pada Dewasa Awal di Bekasi - Fahira, Alsa Zahra; Supriyadi, Tugimin; Abdillah, Rijal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Humans experience a developmental process with various challenges, one of which is the transition from adolescence to early adulthood. At this stage, individuals face feelings of being a “middle man” between adolescence and adulthood, which often leads to self-exploration and increased life demands. One of the significant challenges in this phase is the Quarter Life Crisis (QLC), which usually occurs in the mid-20s. QLC is characterized by concerns about the future, including aspects of finances, interpersonal relationships, career, and self-identity. This crisis triggers emotional and psychological stress due to life changes and instability. In overcoming QLC, self-efficacy plays an important role. Self-efficacy, namely an individual's belief in their ability to face challenges, helps someone manage stress, act effectively, and achieve goals. Individuals with higher levels of self-efficacy tend to be more optimistic, able to face change, and successfully manage life stress. Conversely, low self-efficacy can have detrimental effects on QLC, including feelings of anxiety, fear, and disappointment. Thus, developing self-efficacy is the key to supporting individuals in passing the QLC phase effectively.